Corporate Social Responsibility (CSR) and Profitability Through Bibliometric Analysis - Suraya; Masiyah Kholmi (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study analyzes the development of research on Corporate Social Responsibility (CSR) and profitability conducted by Indonesian scholars during the 2010–2025 period using a bibliometric analysis approach based on Scopus data. A total of 84 articles were examined to identify publication trends, author productivity, and main research themes. The results indicate a significant increase in publications since 2016, peaking in 2020. The most influential authors include Maya Novitasari, Ardi Gunardi, and Veronica Siregar. The dominant research themes focus on the relationship between CSR and profitability, corporate governance, and sustainability. This study confirms that CSR is viewed not merely as a moral obligation but as a sustainable business strategy. However, research collaboration among Indonesian authors remains limited and should be expanded to strengthen Indonesia’s academic contribution to global CSR literature.